Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - and Honig, Daniel (2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT